Hands-on vision and behavior for self-driving cars : explore visual perception, lane detection, and object classification with Python 3 and OpenCV 4 /: explore visual perception, lane detection, and object classification with Python 3 and OpenCV 4. (2020) - Venturi, Luca; Korda, Krishtof
No abstract available